Analisis Kekuatan Struktur Rangka Greenhouse Tipe Single Span Menggunakan Metode Finite Element Analysis - Mas Wisnu Aninditya; Muhammad Salman Fadhil; Kemal Mahfud (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
The structural integrity of greenhouse facilities is fundamental to agricultural safety and productivity, necessitating rigorous analysis of material stiffness and strength to withstand physical loads. This study evaluates the structural feasibility of a single-span greenhouse frame constructed from galvanized iron, specifically comparing the mechanical performance of a design integrated with "W" type support against a conventional frame without additional support. By employing SolidWorks for Finite Element Analysis (FEA), the research determined critical values for Von Mises stress, resultant displacement, and Factor of Safety (FoS). Simulation results revealed that the frame utilizing W-support exhibited superior rigidity, recording a maximum stress of 1.533×107 N/m2, a displacement of 1.105 mm, and a high Factor of Safety of 13.31. Conversely, the frame without W-support demonstrated increased mechanical susceptibility, yielding a maximum stress of 5.517 ×107 N/m2, a displacement of 5.554 mm, and a Factor of Safety of 3.697. Crucially, the stress values obtained for both configurations remained significantly below the galvanized iron's yield strength of 2.039 ×108 N/m2. Consequently, while the W-support design offers enhanced stability, both structural configurations are deemed safe and feasible for agricultural implementation.